Relasi Makna dalam Lirik Lagu Kemiliteran Cakra Kostrad dan Hymne Kostrad - Rijani, Annisa; Ekowati, Sri Harini (Program Studi Magister Linguistik Terapan UNJ, 2023)
This study analyzes the meaning relations in the lyrics of “Cakra Kostrad” and “Hymne Kostrad,” which construct a narrative that reinforces the identity, fighting spirit, and noble values of Kostrad soldiers. The song lyrics are not merely a medium of expression but also serve to build an emotional bond between Kostrad members and their mission to safeguard the sovereignty of the Republic of Indonesia (NKRI). This research uses a qualitative approach with content analysis techniques to explore the symbols, themes, and values contained in the lyrics of “Cakra Kostrad” and “Hymne Kostrad.” The analysis is conducted in three stages: data reduction (identifying symbols, phrases, and keywords), categorization of main themes such as patriotism, sacrifice, and identity, and interpretation of meaning by linking them to military values and distinct symbols like